Reading Trauma in History through Post-Conflict Narrative: Thakuri’s “The Descending Mountain” - Pokharel, Badri Prasad (Molung Educational Frontier, 2020)
Maya Thakuri’s “The Descending Mountain,” is a testimony of an event that might have happened during the People’s War instigated by the Maoists towards the end of the 20th century. It has unfolded the truth hidden behind the curtain, that is, how Nepal’s geopolitical development in the post-democratic movement has made one mass depart towards the forest and raise the voice against those who were still marginalized in the name of caste, gender and ethnicity; which ultimately caused the death of more than fifteen thousand Nepali citizen and hundreds of thousands other displaced from their own homes. The theme of this article is to show a bitter truth that happened in history - the compulsion of perpetrators and victims to sabotage physically and to mourn in trauma. It is to bring the fact of Nepal’s hinterlands’ people’s history of traumatic life – how much traumatic their life was, as well as the reluctance of the civil society to such grave tale. The end of the twentieth century and the beginning of the new era, in political development to grab the power from the elite group have been remarkable to heed for the historians and academicians to knit the very emotional facts in the form of narratives, which is called here post-conflict narrative. Mrs. Thakuri, to some extent, is successful to weave a plot of a mother and her daughter on the background of the People’s War – a historical turning point in the history of Nepal and narrativize the painful traumatic story to the readers.